Digital Humanities and Libraries and Archives in Religious Studies : An Introduction - Clifford B. Anderson (De Gruyter, 2022)
How are digital humanists drawing on libraries and archives to advance research and learning in the field of religious studies and theology? How can librarians and archivists make their collections accessible to digital humanists? The goal of this volume is to provide an overview of how religious and theological libraries and archives are supporting the nascent field of digital humanities in religious studies. The volume showcases the perspectives of faculty, librarians, archivists, and allied cultural heritage professionals who are drawing on primary and secondary sources in innovative ways to create digital humanities projects in theology and religious studies. Topics include curating collections as data, conducting stylometric analyses of religious texts, and teaching digital humanities at theological libraries. The shift to digital humanities promises closer collaborations between scholars, archivists, and librarians. The chapters in this volume constitute essential reading for those interested in the future of theological librarianship and of digital scholarship in the fields of religious studies and theology.